The Legal Protection against Emergency Contacts Made Unilaterally in Online Loans - Chrestella Hana Griselda; Zil Aidi (Law Development Journal, 2023)
The financial development is a pattern of creating new financial instruments in new financial technologies and markets. Financial technology is an innovation in the field of financial services through a touch of modern technology. One example of this innovation is the existence of an online loan company. The purpose of this study is to find out how legal protection is for emergency contacts whose data is listed unilaterally which is misused by online lenders and find out how third party responsibility manifests as an emergency contact in online loans. The type of research used is the type of juridical-normative research. The type of legal material used is secondary legal material.